Monitoring of the Fruit Flies (Bactrocera spp.) Infesting Jujube Orchard using Static Spinosad Traps: Monitoring of Bactrocera spp. by using static spinosad traps - Ariz Muhammad Pirzado; Bhai Khan Solangi; Din Muhammad Soomro; Agha Mushtaque Ahmed; Khadim Hussain Wagan; Faiza Abbasi; Jawad Hyder Soomro; Shafee Muhammad; Abdul Rahman Tunio; Nimra Razzaq (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Fruit flies (Bactrocera spp.) are regarded as serious insect pests of fruits and vegetables in the world. The goal of this study was to examine the effect of spinosad traps on Bactrocera spp. at different heights 0, 1, 2, and 3 m on jujube tree during 2020-2021. Flies’ populations were counted weekly. The results revealed that the highest population of B. zonata (225.6 flies) were recorded at 2 m height on (22 October, 2020) and the lowest ones (21.6 flies) were recorded at the ground level (0 m height) during (4 February, 2021). However, the overall maximum catches were 158.95 at 2 m height and minimum was 68.72 at the ground level. Similarly, the maximum population of B. dorsalis was (50.5 flies) at 2 m height during (9 October, 2020), but the minimum (2.5 flies) was in the ground level during (4 February, 2021). The overall highest B. dorsalis catches were (43.50 flies) at 2 m height and the lowest was (3.55 flies) at ground level. The population of B. zonata correlated positively (r= 0.2939**) with temperature, but negatively (r= -0.0223NS) with relative humidity. However, B. dorsalis populations was positive correlated with both of the temperature and relative humidity (r= 0.0261** and r= 0.0091NS, respectively). Ultimately, pheromone traps (Spinosad+Methyl eugenol) at 2 m height are highly recommended to catches both fruit flies (B. zonata and B. dorsalis) in Jujube Orchards.